Benefit tourism – a new concept of the phenomenon and terminology issues - Różycki, Paweł; Kąkol, Katarzyna (Geotourism/Geoturystyka, 2018)
Benefit tourism is a disputable term. This follows from the fact that the definition of tourism even by UNWTO somehow excludes activities whose aim is to gain financial profit from tourist activities. In the fast changing world we are forced to pose a question whether tourism should still be considered as a relatively narrow concept. While leaving their country for work people also get to know the culture of a visited place since they go sightseeing and, most importantly, they mingle with the natives, and through this they get to know the visited country better. Traditional tourism, especially for those unprepared, does not give a chance to experience the real aspects of the visited country. In commercialized tourism a tourist often gets a distorted picture of the region he/she is visiting. Therefore, a proper preparation (education) together with a right attitude of a person leaving his/her country for work, may be a chance to get to know a different culture, gain a new experience and make a network of contacts. Despite numerous dysfunctions resulting from e.g. separation from a family, the phenomenon has also positive aspects because except from getting to know different regions of the world an economical aim is also accomplished and owing to it, people interested in tourism may either in the future or during weekends pursue their tourist hobbies.